PENGEMBANGAN SOAL NUMERASI MODEL AKM KONTEN ALJABAR SUBDOMAIN RASIO DAN PROPORSI UNTUK JENJANG SMP DENGAN KONTEKS PERSONAL [DEVELOPING AKM MODEL NUMERACY PROBLEMS IN ALGEBRA CONTENT FOR THE RATIO AND PROPORTION SUBDOMAIN AT THE JUNIOR HIGH SCHOOL LEVEL IN A PERSONAL CONTEXT] - Aini, Filda Nur; Kurniati, Dian; Oktavianingtyas, Ervin; Murtikusuma, Randi Pratama; Safrida, Lela Nur (JOHME: Journal of Holistic Mathematics Education, 2024)
The Merdeka Belajar curriculum has been implemented by the Ministry of Education and Culture. There are many programs in Merdeka Belajar curriculum. One of them is the Minimum Competency Assessment (AKM) that measures literacy and numeracy skills. During the implementation of the AKM in 2021, students experienced confusion in understanding the questions because they were not familiar with literacy and numeracy questions. Additionally, students' numeracy skills were low because they did not fully understand the Minimum Competency Assessment questions and had never attempted to work on them. This study aims to develop numeracy literacy questions for the Minimum Competency Assessment. The research type used in this study was Research and Development (R&D), with Thiagarajan's 4-D model chosen as the framework. The 4-D development model consists of four stages: define, design, develop, and disseminate. In the defining stage, observations and analyses of problems occurring in schools were carried out. Subsequently, an initial design of numeracy questions was prepared in the design stage based on data from the previous stage. The initial design then underwent validity and reliability testing in the development stage. The validity test was conducted by three validators, resulting in an average score of 3.89, categorizing the questions as valid. The reliability tests were carried out in a field trial with 26 students, yielding a reliability score of r = 0.607 which is interpreted as high. The results of the practicality test showed an outcome of 86.21%, indicating a very practical category. Numeracy problems that passed the validity, reliability, and practicality tests were distributed both offline and online.BAHASA INDONESIA ABSTRACT: Kurikulum Merdeka Belajar telah diterapkan oleh Kementerian Pendidikan dan Kebudayaan. Ada banyak program dalam Kurikulum Merdeka Belajar, salah satunya adalah Asesmen Kompetensi Minimum (AKM) yang mengukur keterampilan literasi dan numerasi. Selama pelaksanaan AKM pada tahun 2021, siswa mengalami kebingungan dalam memahami soal-soal karena mereka tidak terbiasa dengan soal literasi dan numerasi. Selain itu, keterampilan numerasi siswa rendah karena mereka tidak sepenuhnya memahami soal-soal Asesmen Kompetensi Minimum dan belum pernah mencoba mengerjakannya. Penelitian ini bertujuan untuk mengembangkan soal literasi numerasi untuk Asesmen Kompetensi Minimum. Jenis penelitian yang digunakan dalam studi ini adalah Research and Development (R&D), dengan model 4-D Thiagarajan yang dipilih sebagai kerangka kerja. Model pengembangan 4-D terdiri dari empat tahap: pendefinisian, perancangan, pengembangan, dan penyebaran. Pada tahap pendefinisian, dilakukan observasi dan analisis terhadap masalah yang terjadi di sekolah. Selanjutnya, rancangan awal soal numerasi disiapkan pada tahap perancangan berdasarkan data dari tahap sebelumnya. Rancangan awal tersebut kemudian menjalani pengujian validitas dan reliabilitas pada tahap pengembangan. Uji validitas dilakukan oleh tiga validator, menghasilkan skor rata-rata 3,89, yang mengkategorikan soal tersebut sebagai valid. Uji reliabilitas dilakukan melalui uji coba lapangan dengan 26 siswa, menghasilkan skor reliabilitas r = 0,607 yang diinterpretasikan sebagai tinggi. Hasil uji kepraktisan menunjukkan nilai 86,21%, yang menunjukkan kategori sangat praktis. Soal numerasi yang lolos uji validitas, reliabilitas, dan kepraktisan didistribusikan baik secara offline maupun online.